MODERATION EFFECT OF SOCIAL MEDIA TO ENTREPRENEURIAL DISCOVERY AND CREATION, ANTECEDENT’S PRIOR KNOWLEDGE AND ENTREPRENEURIAL ALERTNESS. AN EMPIRICAL STUDY - Berlilana Berlilana; Tri Wahyuningsih (Universitas Mercu Buana, 2021)
This study aimed to analyze and evaluate the discovery and creation of opportunities in entrepreneurship moderated by social media. Two variables were used as antecedents namely Prior Knowledge and Entrepreneurial Alertness. This research used structural equation modeling method as well as Partial Least Square (PLS) theory. There were 294 final data processed from entrepreneurs who interacted using social media. From the 5 proposed hypotheses, the 5 hypotheses were significantly positive. Prior Knowledge had a significant impact on Entrepreneurial Alertness, social media had a significant impact in moderating Prior knowledge and Entrepreneurial Alertness on finding and creating opportunities. The novelty of this research explores the concept of entrepreneurship in social media and very few researchers conduct research in this field